Transcriptomic and lipidomic analysis of the differential pathway contribution to the incorporation of erucic acid to triacylglycerol during Pennycress seed maturation - Claver, Ana; Luján, María Ángeles; Escuín, José Manuel; Schilling, Marion; Jouhet, Juliette; Savirón, María; López, M. Victoria; Picorel, Rafael; Jarne, Carmen; Cebolla, Vicente L.; Alfonso, Miguel (Frontiers in Plant Science, 2024)
Thlaspi arvense (Pennycress) is an emerging feedstock for biofuel production because of its high seed oil content enriched in erucic acid. A transcriptomic and a lipidomic study were performed to analyze the dynamics of gene expression, glycerolipid content and acyl-group distribution during seed maturation. Genes involved in fatty acid biosynthesis were expressed at the early stages of seed maturation. Genes encoding enzymes of the Kennedy pathway like diacylglycerol acyltransferase1 (TaDGAT1), lysophosphatidic acid acyltransferase (TaLPAT) or glycerol 3-phosphate acyltransferase (TaGPAT) increased their expression with maturation, coinciding with the increase in triacylglycerol species containing 22:1. Positional analysis showed that the most abundant triacylglycerol species contained 18:2 at sn-2 position in all maturation stages, suggesting no specificity of the lysophosphatidic acid acyltransferase for very long chain fatty acids. Diacylglycerol acyltransferase2 (TaDGAT2) mRNA was more abundant at the initial maturation stages, coincident with the rapid incorporation of 22:1 to triacylglycerol, suggesting a coordination between Diacylglycerol acyltransferase enzymes for triacylglycerol biosynthesis. Genes encoding the phospholipid-diacylglycerol acyltransferase (TaPDAT1), lysophosphatidylcholine acyltransferase (TaLPCAT) or phosphatidylcholine diacylglycerolcholine phosphotransferase (TaPDCT), involved in acyl-editing or phosphatidyl-choline (PC)-derived diacylglycerol (DAG) biosynthesis showed also higher expression at the early maturation stages, coinciding with a higher proportion of triacylglycerol containing C18 fatty acids. These results suggested a higher contribution of these two pathways at the early stages of seed maturation. Lipidomic analysis of the content and acyl-group distribution of diacylglycerol and phosphatidyl-choline pools was compatible with the acyl content in triacylglycerol at the different maturation stages. Our data point to a model in which a strong temporal coordination between pathways and isoforms in each pathway, both at the expression and acyl-group incorporation, contribute to high erucic triacylglycerol accumulation in Pennycress.